Prevalence of Malnutrition in Bhal Region of Gujarat State - Gayatree Jadeja; M. S. Jakasaniya (Indian Journal of Extension Education, 2017)
There has been increasing evidence that development of underweight and obesity has deleterious social and health consequences. The study was conducted to determine the prevalence of underweight and obesity in rural areas of Bhal region of Gujarat state. Total of 1213 subjects of four different age groups were selected from different 80 villages of rural area. The height, weight were measured for all age groups. Mid upper arm circumference, hair colour and skin texture were observed for preschool children as well as the blood pressure was measured for adults above 40 years. All parameters were correlated with the body mass index. The results found were alarming. Majority of girls had malnourishment symptoms compared to boys. More of tobacco addiction was found in adult male and 40 to 49 years adults were suffering from high blood pressure problem. Illiteracy was higher in female which is indirectly responsible for the health of the community